A novel ACE2 activator reduces monocrotaline-induced pulmonary hypertension by suppressing the JAK/STAT and TGF-β cascades with restored caveolin-1 expression. (1st February 2015) - Haga, Shiori; Tsuchiya, Haruka; Hirai, Toshitake; Hamano, Takaichi; Mimori, Akio; Ishizaka, Yukihito
ABSTRACT Introduction: Pulmonary hypertension (PH) is characterized by increased pressure in the pulmonary artery and right ventricular hypertrophy (RVH). Recently, angiotensin-converting enzyme 2 (ACE2), which converts angiotensin (Ang) II into Ang-(1-7), was shown to inhibit experimental PH. Here we identified a novel ACE2 activator and investigated how the compound reduced monocrotaline (MCT)-induced PH. Methods: To induce PH, Sprague-Dawley rats were injected subcutaneously with MCT, followed by the continuous administration of NCP-2454, an ACE2 activator, using osmotic pumps. Pulmonary arterial compliance was monitored every week until 4 weeks post-injection (wpi). RVH and lung remodeling was evaluated using lung tissue at 4 wpi. Results: NCP-2454 upregulated the production of Ang-(1-7) when incubated with ACE2 and Ang II. Notably, a continuous infusion of NCP-2454 significantly improved pulmonary arterial compliance, right ventricular systolic pressure, and RVH in MCT-treated rats. Interestingly, NCP-2454 increased the relative expression of ACE2 and MAS mRNA in lung tissue, especially in MCT-treated rats. In addition, the compound inhibited the MCT-induced overexpression of transforming growth factor β, phosphorylation of signal transducer and activator of transcription-3 (STAT3), and interleukin-6 production. The compound also restored the expression of caveolin-1 (Cav-1), which negatively regulates the Janus kinase-STAT signaling cascade. Conclusions: NCP-2454 prevented MCT-induced PH by suppressing intracellular inflammatory cascades, an upstream molecular change of which is the disruption of Cav-1 expression.